In Vitro Heavy Metals Inhibitive Assay Using the Acetylcholinesterase from Osteochilus hasselti (Cyprinid Fish) (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
Rapid industrial development has caused many hazardous toxicants, especially heavy metals, to be released directly or indirectly into the environment which resulted in the polluted environment, mainly the water bodies. There are numerous Malaysian rivers that are largely polluted by heavy metals which can cause negative impact on health of public as well as the environment. Hence, a rapid and simple biomonitoring method will aid in notifying government agencies as well the public to such threat. Accordingly, acetylcholinesterase (AChE) inhibition has been widely used as a biomarker for heavy metals detection. In this study, the potential of AChE from Osteochilus hasselti brain as an alternative biosensor for heavy metals detection is measured. We discovered that out of seven heavy metals tested at the final concentration of 5 mg/L, only Hg2+, Ag2+, and Cu2+ exerted more than 50% significant inhibition (p 0.05) compared to each other. Meanwhile, the Cr6+ and Pb2+ showed no notable inhibitory effect on the activity of AChE. The results exhibited that AChE of O. hasselti has the capability to be used as a biosensor for the detection of metal ions.
Keywords: Osteochilus hasselti; acetylcholinesterase; heavy metals; in vitro assay; biomonitoring